1999
DOI: 10.1093/ajcn/70.5.892
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum ubiquinone-10 concentrations in phenylketonuria

Abstract: Serum ubiquinone-10 deficiency appears to be related to the restricted diet of PKU patients. Because serum ubiquinone-10 plays a major antioxidant role in the protection of circulating lipoproteins, the correction of ubiquinone-10 concentrations should be considered in PKU patients. Further investigation seems advisable to elucidate whether the deficiency in serum ubiquinone-10 status is clinically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 20 publications
3
35
0
2
Order By: Relevance
“…Numerous studies have provided experimental evidence demonstrating oxidative stress in human PKU patients and animal models (Artuch et al, 2001(Artuch et al, ,2004Colome et al, 2003;Ercal et al, 2002;Martinez-Cruz et al, 2002;Sierra et al, 1998;Sirtori et al, 2005). Our laboratory previously demonstrated increased inducible nitric oxide synthase production by infiltrative cd11b macrophage cells in the mesencephalon and hypothalamus of PKU mice (Embury et al, 2005), providing further evidence of oxidative processes occurring in these regions.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Numerous studies have provided experimental evidence demonstrating oxidative stress in human PKU patients and animal models (Artuch et al, 2001(Artuch et al, ,2004Colome et al, 2003;Ercal et al, 2002;Martinez-Cruz et al, 2002;Sierra et al, 1998;Sirtori et al, 2005). Our laboratory previously demonstrated increased inducible nitric oxide synthase production by infiltrative cd11b macrophage cells in the mesencephalon and hypothalamus of PKU mice (Embury et al, 2005), providing further evidence of oxidative processes occurring in these regions.…”
Section: Discussionmentioning
confidence: 73%
“…Ercal et al (2002) provided experimental evidence of oxidative damage in Pah enu2 mice that included increased concentration of the lipid peroxidation by-product malon-dialdehyde in brain tissue, decreased glutathione/glutathione disulfide also in brain and increased catalase and glucose-6-phosphate dehydrogenase in erythrocytes of these animals. Other studies indicating the role of oxidative stress in PKU include human studies by Artuch et al (2001Artuch et al ( , 2004; Colome et al (2003);and Sierra et al (1998). Sirtori et al (2005) demonstrated the involvement of oxidative stress in human PKU patients through increased levels of thiobarbituric acid reactive species (indicative of lipid peroxidation) and decreased total antioxidant reactivity, suggestive of deficient capacity to handle increases in reactive species.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the normal glutathione values observed in our PKU patients would further support the beneficial effects of low tHcy and cysteine concentrations. However, this hypothesis should be considered with caution because other factors present in PKU patients may increase oxidative stress, such as selenium deficiency in patients with poor dietary adherence (Van Bakel et al, 2000), or the decreased ubiquinone-10 values observed in serum (Artuch et al, 1999) and cells (Colomé et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In PKU, deficiencies in two important antioxidants, selenium (Van Bakel et al, 2000) and coenzyme Q10 (Artuch et al, 1999), have been reported. These deficiencies were mainly related to poor dietary compliance, and might cause an increase in peroxidative damage manifested in high malondialdehyde (MDA, a product of lipid peroxidation) values, low reduced glutathione concentrations and/or low normal tocopherol concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, apart from the bioenergetic function, quinones are considered to be engaged in a variety of cellular functions that are not only associated with their redox properties but also with the capability to change the fluidity of the lipid bilayers (48,96,256). The later point is supported by the fact that occurrence of quinones is not restricted to mitochondrial membrane (91), and the changes in their content is also correlated with age and with several diseases (10,86,87,138,156,167,263).…”
Section: Quinones and The Q Poolmentioning
confidence: 99%